AN EXAMINATION OF THE CAUSES AND EXPERIENCES OF ELDERLY RESIDENTS IN KUSHTIA DISTRICT: THE RISE OF OLD AGE HOMES IN BANGLADESH - Sobnur Hena; Nafiul Muid Muid; Dr. Md. Ruhul Amin; Morium khatun (Yayasan Wayan Marwan Pulungan, 2026)
In Bangladesh, population aging is a significant issue because the number of older persons is increasing rapidly, following a decline in fertility and improvements in life expectancy. This qualitative exploratory study aimed to examine the antecedents of how older adults end up in nursing homes and their emotional/psychosocial experiences within these facilities. In this sense, the study identified several key themes based on personal interviews with residents of a government-registered nursing home in the Kushtia district of Bangladesh (n = 15). Thematic analysis indicated that the abuse and neglect by family members, in particular, adult children and daughters-in-law, are significant causes of institutionalization, accompanied by financial crisis, declining health, and absence of available caregivers. The changing demographics, characterized by decreasing fertility rates and the migration of young generations to new cities, have eroded traditional family support systems. Although the nursing home offers protection and some basic needs, most of the people who live there still suffer emotionally, feel lonely, and are dying to see and embrace their families. The Attachment Theory by Bowlby helps explain why the loss of primary caregivers leads older people to seek a safe place in institutions. The results emphasize the need to tighten laws, social security systems, and community-based geriatric interventions to support families in providing dignified care for the aging population in Bangladesh. Mental health services can be incorporated in nursing homes, further benefiting the health of older people who are institutionalized.